2020
DOI: 10.1007/s00345-020-03229-5
|View full text |Cite
|
Sign up to set email alerts
|

Additional surgical procedures and perioperative morbidity in post-chemotherapy retroperitoneal lymph node dissection for metastatic testicular cancer in two intermediate volume hospitals

Abstract: Purpose To evaluate the perioperative morbidity of PC-RPLND in two intermediate volume centers and to identify predictors of high morbidity. Methods Retrospective analysis of 124 patients treated with open PC-RPLND at two tertiary referral centers between 2001 and 2018. Perioperative morbidity was determined by analyzing additional surgical procedures, intra-operative blood loss, and postoperative complications. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…No perioperative mortality was observed in our series, which is consistent with other recent reports [8,13,27,30,31,33,34,36]. Low mortality rates of 0.20 to 1.6% [12,29,32,35,38,39] were reported in some other studies ( Table 5). In a Dutch series, one death due to anaesthesiological problems was reported [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No perioperative mortality was observed in our series, which is consistent with other recent reports [8,13,27,30,31,33,34,36]. Low mortality rates of 0.20 to 1.6% [12,29,32,35,38,39] were reported in some other studies ( Table 5). In a Dutch series, one death due to anaesthesiological problems was reported [40].…”
Section: Discussionsupporting
confidence: 93%
“…An overview of contemporary studies providing data on grade III-V complications utilizable for comparison is given in Table 5. Five studies reported higher rates than the present series [27][28][29][30][31], 10 lower [8,12,15,[32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 50%
“…On the condition that oncological safety is warranted, this may provide significant benefit to patients. After all, the morbidity of open PC-RPLND is high, while histopathology of the retroperitoneal specimen shows fibrosis or necrosis in a large proportion of patients [3,4,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This incidence is comparable to that in the literature, with rates of 34% to 71%. 4,6,7,16,18 The resection/reconstruction of venous vessels is much more common than that of arteries. The second most resected organ in our analysis was the kidney in 32% of patients with adjacent resection, with 33% of them harboring only N. In most other studies, nephrectomy was also the second most resected organ, with 15% to 42% of patients undergoing adjacent resections.…”
Section: Adjunctive Surgery Perioperative Complications and Oncologic...mentioning
confidence: 99%
“…The second most resected organ in our analysis was the kidney in 32% of patients with adjacent resection, with 33% of them harboring only N. In most other studies, nephrectomy was also the second most resected organ, with 15% to 42% of patients undergoing adjacent resections. 4,6,7,16,18,19 A partial hepatectomy was performed in 21% of studied patients, with N being present in 54% of patients. Other studies reported a frequency of 6% to 19% with a partial hepatectomy within patients undergoing adjunctive surgery.…”
Section: Adjunctive Surgery Perioperative Complications and Oncologic...mentioning
confidence: 99%